Willingness to Work and the Working Environment of Japanese Dental Hygienists - Yoshiaki Nomura; Ayako Okada; Jun Miyoshi; Masaru Mukaida; Eriko Akasaka; Keietsu Saigo; Hideki Daikoku; Hidenori Maekawa; Tamotsu Sato; Nobuhiro Hanada (Hindawi Limited, 2018)
Japanese dental hygienists' employment rate is low. The environment factors and daily job contents that contribute to willingness to work of Japanese dental hygienists and their structures were investigated. A cross-sectional survey was conducted using a self-administered postal questionnaire distributed for one thousand and twenty-three members of Japan Dental Hygienist Association registered in Iwate prefecture affiliation. Three items concerning willingness to work, satisfaction for the 9 items about working environment, anxiety for work, and 106 daily job contents were used for analysis. Structural equation modeling, decision analysis, and correspondence analysis were carried out. The present study found that working environment such as interpersonal relationship was more important than social environment such as salary for the regular employee of Japanese dental hygienist working at private dental office. However, salary was only the determinant for the dental hygienist who strongly disliked their work. And daily job contents affected the willingness to work. Especially, jobs concerned with prosthodontic treatments were of major concern. Improving the working environment and avoiding assignment of tasks that require lower level of skill may improve dental hygienists' willingness to work and may assist to improve the employment rate of dental hygienist in Japan.